2017
DOI: 10.7575/aiac.alls.v.8n.6p.141
|View full text |Cite
|
Sign up to set email alerts
|

Item Analysis of a Multiple-Choice Exam

Abstract: Although foreign language testing has been subject to some changes in line with the different perspectives on learning and language teaching, multiple-choice items have been considerably popular regardless of these perspectives and trends in foreign language teaching. There have been some studies focusing on the efficiency of multiple choice items in different contexts. In Turkish context multiple choice items have been commonly used as standardized stake holder tests as a requirement for undergraduate level f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
1
14
0
7
Order By: Relevance
“…Con todo lo anterior, y ante la necesidad de consolidar una prueba de clasificación válida y confiable, se optó iniciar los estudios estadísticos de la misma con la medición de los Índices de Dificultad (en adelante IF, por sus siglas en inglés) y de discriminación (en adelante ID, por sus siglas en inglés). Si bien estos no son los únicos estudios estadísticos que se pueden aplicar a una prueba, sí constituyen un punto de partida, según lo establecen los antecedentes consultados en la revisión bibliográfica (Janssen & meier, 2013;Toksöz & Ertunç, 2017;Sugianto, 2020). A continuación, se definen ambos índices.…”
Section: El Análisis De íTems En Pruebas De Lenguaunclassified
See 2 more Smart Citations
“…Con todo lo anterior, y ante la necesidad de consolidar una prueba de clasificación válida y confiable, se optó iniciar los estudios estadísticos de la misma con la medición de los Índices de Dificultad (en adelante IF, por sus siglas en inglés) y de discriminación (en adelante ID, por sus siglas en inglés). Si bien estos no son los únicos estudios estadísticos que se pueden aplicar a una prueba, sí constituyen un punto de partida, según lo establecen los antecedentes consultados en la revisión bibliográfica (Janssen & meier, 2013;Toksöz & Ertunç, 2017;Sugianto, 2020). A continuación, se definen ambos índices.…”
Section: El Análisis De íTems En Pruebas De Lenguaunclassified
“…Por otra parte, el ID hace referencia al potencial que tiene un ítem para distinguir a los examinados con mejor nivel de los examinados con nivel inferior (Brown, 2004;Carr, 2011;Toksöz & Ertunç, 2017). Si un ítem obtiene respuestas correctas de la mayoría de examinados de nivel alto, y respuestas incorrectas de la mayoría de examinados de nivel bajo, entonces dicho ítem es apropiado para diferenciar entre examinados de proficiencia alta y de proficiencia baja.…”
Section: El íNdice De Dificultad (If) Y El íNdice De Discriminación (Id)unclassified
See 1 more Smart Citation
“…Their Study was conducted at department of Pathology, Islamabad medical and dental college. Toksöz and Ertunç (2017) conducted an item analysis of MCQ exam in language and literary studies. They found that most of used items were at moderate level and their results classified 28% of the items in low item discrimination value.…”
Section: Introductionmentioning
confidence: 99%
“…MCQs are very popular in language testing today although foreign language testing has changed in line with the different perspectives on language learning and teaching, [7]. MCQs or "items" are often applied to assess students in various examinations throughout the world for their objectivity and broad coverage in a shorter time [8].…”
Section: Introductionmentioning
confidence: 99%